Quantifying Decoherence in Attosecond Metrology - C. Bourassin-Bouchet (American Physical Society, 2020)
Laser-dressed photoemission spectroscopy has established itself as the gold standard of attosecond temporal metrology. In this technique, the attosecond structure of an extreme-ultraviolet pulse is retrieved from the wave function of the electron wave packet released during photoionization. Here, we show that this electron wave packet should rather be described using the density matrix formalism, thus allowing one to account for all processes that can affect its coherence, from the attosecond pulse generation to the photoemission and the measurement processes. Using this approach, we reconstruct experimentally a partially coherent electron wave packet with a purity of 0.11 (1 for full coherence). Comparison with theoretical models then allows us to identify the origins of this decoherence and to overcome several limitations such as beam-line instabilities or spectrometer resolution. Furthermore, we show numerically how this method gives access to the coherence and eigencomponents of complex photoelectron wave packets. It thus goes beyond the current measurement of photoionization time delays and provides a general framework for the analysis and understanding of complex photoemission processes.